Association between metabolic syndrome and homocysteinemia in ischemic stroke - Milorad Vujnić; Alma Prtina; Tatjana Milivojac (Биомедицинска истраживања, 2021)
Introduction: Stroke is one of the leading causes of morbidity and mortality worldwide. The relationship between metabolic syndrome (MetS) and homocysteinemia (Hcy) as risk factors for ischemic stroke (IS) is not completely clear. The aim of the study was to determine the frequency of MetS, serum level of Hcy and the frequency of hyperhomocysteinemia (HHcy), as well as their association in patients with IS. Methods: The research included 53 subjects being in rehabilitation after IS and 40 subjects in the control group in rehabilitation due to the back pain problems aged 50-70 years. The diagnosis of the ischemic stroke was established by insight in the medical documentation. All subjects had to have a diagnosis of stroke confirmed by imaging (CT or MR of the endocranium). All subjects in the control group were excluded from the existence of previous stroke, myocardial infarction, angina pectoris and peripheral vascular disease. MetS was defined according to the joint statement from 2009. Results: The frequency of MetS was significantly higher in patients with IS compared to the control group (88.7% vs. 70.0%, p<0.05). The level of Hcy and the frequency of HHcy were increased in the patients with stroke compared to the control group (15.0±5.50 µmol/L vs. 11.2±2.51 µmol/L, p<0.01 and 39.2% vs. 11.4%, p<0.01, respectively). Among patients with IS, those with MetS had higher frequency of HHcy (42.2% vs. 16.7%, p<0.05) and it increased with more individual components of MetS (11.1% in patients with 3 components, 36.8% in patients with 4 components and 64.7% in patients with 5 components, p<0.05). Hcy was also in positive correlation with serum triglyceride level. Conclusion: Our results suggest that MetS and Hcy represent a significant risk factors for IS. It seems that there is an association between these risk factors in pathogenesis of the IS, but further analyses are needed to confirm this hypothesis.
Keywords: ischemic stroke; metabolic syndrome; homocysteine; atherosclerosis; obesity